The Reformation and the Renaissance (1485-1547) : Second Edition - Bewsher, F. W. (Frederick William), 1886-1950; Bell, Kenneth (Kenneth Norman), 1884-1951; Winbolt, S. E. (Samuel Edward), 1868-1944 (Salt Lake City, UT : Project Gutenberg, 2016)
"The Reformation and the Renaissance (1485-1547)" by Bewsher, Bell, and Winbolt is a historical account compiled in the early 20th century. This work serves as a sourcebook for studying the key documents and events surrounding the English Reformation and Renaissance period, focusing particularly on the transformative years of Henry VIII's reign. It likely aims to equip students and scholars with original texts that illustrate the significant political, social, and religious changes occurring during this time. At the start of the book, the introduction outlines the authors' intention to provide valuable historical documents for educational purposes. They emphasize the need for accessible materials that foster active engagement with history. The opening sections present various documents, beginning with ceremonial details related to the coronation of Henry VII, followed by accounts of significant occurrences like the introduction of the Yeomen of the Guard, the Sweating Sickness epidemic, and Lambert Simnel$1 (Bs rebellion. This selection sets the stage for exploring the historical trajectory leading to the Reformation, capturing the political intrigues and social dynamics of the late 15th and early 16th centuries. (This is an automatically generated summary.)s
Release date is 2016-02-16
E-text prepared by Chris Pinfield and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Reformation -- England; Great Britain -- History -- Tudors, 1485-1603 -- Sources